Management of orbital floor fractures-A case series - Shanmugam, Devakumari; Thanasekar, Vijhayapriya (Asian Journal of Medical Sciences, 2021)
Orbital floor fractures are the most challenging fractures to be managed in maxillofacial region. They are diagnosed in isolation or in combination with mid face fractures, Lefort fractures and zygomatic fractures. The treatment depends on the displacement of the fractured bones and the manifestations of muscle entrapment elicited by clinical examination and radiographic assessment. The timing of repair is of paramount importance and decided on the case to case basis. Proper surgical approach along with appropriate implant placement is the key to success. This paper describes a series of 11 patients operated in IGMC&RI, Puducherry for orbital floor fractures from 2010 to 2019.